The Integration of National Insight In Hidden Curriculum - Safitri Khoirinindyah; Anita Puji Astutik (State Islamic Institute of Madura, 2021)
This study aims (1) to develop the material on national insight in the hidden curriculum. (2) Examining the validity, practicality, and effectiveness of the integration of national insight in hidden curriculum. The method used in this research is development research (R&D / Research and Development). This study raises based on the theory that setted up by Borg and Gall by using 9 steps in the study. The sampling in this research is using probability sampling techniques with 75 students as the sample. The data collection technique in this study is using a questionnaire. The technique that applied in this research is one sample t-test technique. The results of this study are (1) this development research is able to integrate national insight into the hidden curriculum, (2) the validity value obtained from the national insight material is 83 and is declared feasible. The practicality value obtained from the national insight material is 86%. The development of this material in the hidden curriculum was declared effective by the difference in the mean of the pretest results of 71,32 and the posttest results of 81,48. So, it can be concluded that the national insight is very feasible and effective to applied in the hidden curriculum.